Demand Analysis of FAFH in Malaysia - Alias, Radam; Shazali, Abu Mansor; Dyg Affizzah, Awang Marikan (2004)
Despites the importance of FAFH, limited attempt has been made to study the economics of this emerging cultural change. This may be due to underestimation of importance of FAFH, especially when the food sector is mostly studied at aggregate level. The general objective of this study is to analyze FAFH consumption in Malaysia. Specifically, the objective of this research is to analyze the determinants of FAFH demand and examine how socioeconomic factors of consumers have contributed to FAFH. The control variables for the study provided expected coefficients that are significantly different than zero. As the level of development increase, household structure changes simultaneously with income increase that lead to an increase in FAFH expenditure. This study has shown that FAFH has the propensity to increase with an increase in income. FAFH high-income elasticity provides a good indicator for FAFH industry demand.